Parallelization analysis on clusters of multicore nodes using shared distributed memory parallel computing models - Tinetti, Fernando Gustavo
This paper presents alternatives performance results obtained by analyzing parallelization on a cluster of multicore nodes. The ultimate goal is to if both shared distributed memory parallel processing models need to be taken into account independently, if one affects the other both must be considered simultaneosly. The application used as a testbed is classical in the context of highperformance computing: matrix multiplication. Results are shown in terms of the conditions under which performance is optimized to focus the parallelization efforts on clusters with nodes with multiple cores, based on experiments combining both kinds of parallel models. In any case, processing units should be effectively used in order to optimize the performance of parallel applications.